Observation of D0−D[bar]0 oscillations - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
We report a measurement of the time-dependent ratio of D0→K+π− to D0→K−π+ decay rates in D*+-tagged events using 1.0 fb−1 of integrated luminosity recorded by the LHCb experiment. We measure the mixing parameters x'2=(−0.9±1.3)×10−4, y′=(7.2±2.4)×10−3, and the ratio of doubly-Cabibbo-suppressed to Cabibbo-favored decay rates RD=(3.52±0.15)×10−3, where the uncertainties include statistical and systematic sources. The result excludes the no-mixing hypothesis with a probability corresponding to 9.1 standard deviations and represents the first observation of D0−¯¯¯D0 oscillations from a single measurement.
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 582
Im Titel ist "0" hochgestellt
Im Titel steht der zweite Buchstabe D mit einem Oberstrich
Gesehen am 23.03.2021